“Gestión Administrativa y su incidencia en la calidad del servicio al cliente de la Cooperativa de Ahorro y Crédito Sinchi Runa Ltda del cantón La Maná, provincia de Cotopaxi, Año 2020” - Guamán Yasaca, Martha Alexandra (2020)
The purpose of this research project was to analyze the administrative management and its impact on the quality of customer service of the Cooperative de Ahorro y Crédito Sinchi Runa Ltda. Of the canton Maná, which was proposed to address several deficiencies such as: low level of training on administrative issues that allow achieving optimal efficiency of the cooperative's resources. For this, an analytical methodology was used that made it possible to identify the causes and effects of the existing problem; The deductive method will infer on the general premises of administrative management, the bibliographic research provided the opportunity to scientifically substantiate the content of the proposal, the field research was present during the collection of information, the results of which were presented graphically and explained by means of descriptive research. The diagnosis made through the interview with the Head and Agency established that there is no administrative management model defined in a documentary manner. Regarding the quality of service, it is not adequate, because the partners showed dissatisfaction with several aspects evaluated, administrative management has a relevant impact on the quality of service, for this reason the design of a model was proposed of administrative management that included strategies such as: training suggestions for the administrative area, the essential profile for the position of the Head of Agency, planning strategies, organization, direction, control, suggestions for external and internal alliances with local institutions and the design of flow charts of the processes of opening savings accounts, obtaining credits and fund-raising. These strategies, when applied, will allow for efficient administrative management and improvement of the quality of the service provided to its clients.